Pola dari Dinas Pemberdayaan Masyarakat dan Desa dalam Penguatan Kapasitas Pemerintah Desa di Kabupaten Sinjai - Abdillah, Ashar; Darmawati, Darmawati; Baharuddin, Arhan (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2024)
This research​ aims to explain the draft from Service Empowerment Public And Village Regency Sinjai regarding the frame increase capacity apparatus village. Technique study is a method qualitative, study This in the data collection process includes observation, interviews, and documentation. As for the informant on the study the head of the Sinjai Regency Community and Village Empowerment Service, Head of Field Government Village, Governance Section​ Village, Sexy Development Capacity Apparatus Village, Apparatus Villages in the Regency Sinjai. The technique developed data analysis that is Data Reduction, Presentation Data, and Data Verification. The draft from Service Empowerment Public And Village increases the capacity of the government village with mentoring, training, and most importantly, building coordination between government villages in support of the governance process of managing government villages. Village build Indonesia into beginning resurrection village with supported with its publication Law about The expected village as material guidelines in maintenance government village. On maintenance government in the village Still becomes a task together in an independent village especially with various innovations of course the more improved for progress village. PMD Department is an institution of government villages that have tasks to accommodate government villages.